Quantification of Leadership Change: A Case Study on the Gujarat State - REDDY, G DIVAKARA; THAIYALNAYAKI, M; THAIYALNAYAKI, M (International Journal of Psychosocial Rehabilitation, 2020)
In this technocractic age the difference between management and leadership is narrowed down to zero now both are easily interchangeable. This paper is mainly focused to measure leadership effectiveness in the political arena with respect to economic development. This paper is contemplated to quantify the leadership effectiveness after leadership change which is purely subjective in nature.